Ephrin‐B2 overexpression predicts for poor prognosis and response to therapy in solid tumors. Issue 3 (1st November 2016) - Oweida, Ayman; Bhatia, Shilpa; Hirsch, Kellen; Calame, Dylan; Griego, Anastacia; Keysar, Steve; Pitts, Todd; Sharma, Jaspreet; Eckhardt, Gail; Jimeno, Antonio; Wang, Xiao Jing; Parkash, Gill; et al.
Abstract : Ephrin B2 is variably expressed on tumor cells and its blockade has been shown to inhibit angiogenesis in animal models of pancreatic, colorectal, lung and head, and neck squamous cell carcinomas. However, the implications of ephrinB2 expression in cancer patients have remained elusive. In this study, we analyzed the cancer genome atlas (TCGA) for ephrinB2 expression. We report significant correlations between EFNB2 expression, overall survival and disease‐free survival in head and neck squamous cell carcinoma (HNSCC, n  = 519), pancreatic adenocarcinoma ( n  = 186), and bladder urothelial carcinoma ( n  = 410). In HNSCC patients, high‐EFNB2 mRNA expression was associated with tumor HPV negativity, oral cavity location, alcohol intake, higher TP53 mutation, and EGFR amplification. EphrinB2 overexpression also correlated with worse response to chemotherapy and radiotherapy. The therapeutic potential of blocking ephrinB2 was validated in HNSCC patient‐derived tumor xenografts and showed significant improvement in survival and tumor growth delay. Our data shows that ephrinB2 overexpression can serve as a critical biomarker for patient prognosis and response to therapy. These results should guide design of future clinical trials exploring EphrinB2 inhibition in cancer patients. © 2016 Wiley Periodicals, Inc.